Concentrating ammonium in wastewater by forward osmosis using a surface modified nanofiltration membrane. Issue 2 (13th December 2018) - Jafarinejad, Shahryar; Park, Hosung; Mayton, Holly; Walker, Sharon L.; Jiang, Sunny C.
Abstract : Enhancing ammonium rejection by PEI modification. Abstract : Municipal wastewater contains a high concentration of nitrogen in the form of ammonium, which pollutes the environment if not properly removed before discharge. However, the energy intensive processes necessary to convert the biologically available forms of nitrogen into the unfixed elemental form (N2 ) during wastewater treatment contradict the costly industrial efforts to achieve the opposite ( i.e. Haber process) for production of nitrogen fertilizers for agricultural uses. Recovery of ammonium from domestic wastewater should be a priority for wastewater treatment plants to convert the waste into resources. This study reports developing a surface modified nanofiltration membrane operating in forward osmosis mode for concentrating ammonium in wastewater. Surface modification was accomplished using dicyclohexylcarbodiimide (DCC) as a cross-linking agent to graft polyethylenimine (PEI) on the polyamide (PA) thin film composite (TFC) membrane. Changes in membrane surface chemical structure and zeta potential demonstrated the successful incorporation of PEI. The modified membranes had similar surface roughness to the virgin membrane but improved hydrophilicity. Filtration tests using synthetic ammonium solutions demonstrated improved water flux and reduced reverse solute (Mg 2+ and Cl − ions) flux in some of the modified membranes. All PEI grafted membranes had improved ammonium rejection for synthetic ammonium solutions as well as a secondary return activated sludge sample from a wastewater treatment plant. Ammonium rejection by the modified membranes was greater than 99% for the synthetic ammonium solution. The rejection rate declined to 89.3% for treating real wastewater but was much improved in comparison to 75.5% rejection by the virgin membrane. PEI-modified membranes present a potential technology for the collection and reuse of ammonium from wastewater sources.